Intensitas Persediaan, Ukuran Perusahaan, dan Agresivitas Pajak: Koneksi Politik sebagai Variabel Moderasi - Ayu Rida Siciliya (Jurnal Literasi Akuntansi, 2021)
Purpose: This study aim to examine inventory intensity, firm size and tax agrresiveness: political connection as moderating variables. Method: The method in this study using purposive sampling method and obtained 40 companies with data processed 176 annual financial statements. This research technique uses multiple linear and Moderated Analysis Moderated. Finding: The findings in this study that inventory intensity has a negative effect on tax aggressiveness, and firm size has a positive effect on tax aggressiveness. Political connection cannot moderate the negative effect of inventory intensity on tax aggressiveness, and political connection can weaken the positive effect of firm size on tax aggressiveness.  Novelty: The difference between this study and previous research is that this research tries to integrate several topics regarding the variable of tax aggressiveness practices which are influenced by two variables including inventory intensity, and firm size, using the moderating variable of political connection